2016
DOI: 10.1002/prca.201600078
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope metabolic labeling suggests differential turnover of the DPYSL protein family

Abstract: In vivo N metabolic labeling allows the simultaneous investigation of protein expression and turnover, enabling detailed protein dynamics studies. We report for the first time protein turnover data for the DPYSL2, DPYSL3, and DPYSL5 protein family members. As DPYSL proteins have important functions for nervous system maturation, our data provide useful information on their molecular fate during brain development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The CRMP family consists of CRMP1-5 (30)(31)(32), some studies have shown that CRMP4 expression is low in PCa. The methylation of CRMP4 promoter leads to a downregulation of CRMP4, which further promotes the invasion and metastasis of PCa and affects the prognosis (18,24,33).…”
Section: Discussionmentioning
confidence: 99%
“…The CRMP family consists of CRMP1-5 (30)(31)(32), some studies have shown that CRMP4 expression is low in PCa. The methylation of CRMP4 promoter leads to a downregulation of CRMP4, which further promotes the invasion and metastasis of PCa and affects the prognosis (18,24,33).…”
Section: Discussionmentioning
confidence: 99%
“…Among the differentially expressed proteins identified by MALDI-TOF/TOF MS in the present study, several of these have a potential role in nerve growth and differentiation. DPYSL2 belongs to the DPYSL family of proteins (29), which includes five members; these proteins serve important roles in the maturation of the nervous system in humans and in rats (30). DPYSL2, also reported as collapsin response mediator protein 2, and isocitrate dehydrogenase (NADP) have been proposed to be plasma membrane-associated proteins involved in neuronal differentiation, axon growth and guidance, neuronal growth cone collapse and cell migration (31).…”
Section: Discussionmentioning
confidence: 99%
“…Although not specifically used for detection of newly synthesized proteins but able to label whole animals, in vivo metabolic labeling using heavy isotope 15 N was described in several studies. For example, for quantification of Drosophila (fruit fly) proteomes [45], for preparation of 15 N-labeled protein standards from mice to compare unlabeled proteomes [46], for identification of variation in expression and turnover of dihydropyrimidinase-related proteins DPYSL3 and DPYSL5 during brain development by incorporation of 15 N into mice diet [47], and for determination of protein turnover rates on whole proteome scale by restricting all the nitrogen in the rodent diet to 15 N (spirulina algae) with reversion to normal 14 N diet with time points at days to years [48]. In addition, there have been various reviews published discussing both the strengths and the weaknesses of chemical and metabolic labeling of model organisms [49], the merits and difficulties of labeling methods for assessing protein turnover and dynamics [5051], and a review article of stable isotopes and mass spectrometry in life sciences covering a time period from 1920 to 2016 [52].…”
Section: Strategy and Methods To Identify Newly Synthetized Proteins mentioning
confidence: 99%